Інформаційні технології візуального аналізу даних екологічного моніторингу - Каменева, І.П.; Артемчук, В.О. (Моделювання та інформаційні технології, 2011)
We propose an integrated information technology of analysis of data for environmental monitoring and identifying risks, including GIS-visualization technology technogenic loads on geographically distributed systems. The structure of software and information management for the problems of analysis and visualization of man-made pressures on the local and regional level.